A proteção ético-jurídica dos dados genéticos humanos em atividades de biobancos, à luz da Constituição Federal de 1988 e das diretrizes internacionais - Bellarmino , Clarissa Lopes (2018)
Scientific research involving human beings, carried out in the biomedical and genetic areas, generates data from activities developed in biobank, among which genetic data, which should be protected not only in the ethical scope, but also in the legal sphere. Genetic data are information related to hereditary characteristics obtained from samples of human biological sources (eg: cells, hair, tissues, blood, bone, tumors and organs, among other materials derived from human body). These samples can be stored, processed and accessed on biobank - nonprofit structure, organized and systematized in universities and research institutions that provides technologies and/or equipment necessary for scientific investigation. The purpose of this study is to verify whether current Brazilian regulation is sufficient or not regarding the ethical-legal protection of human genetic data in biobank activities, considering the rights of the participants, as far as safeguarding their personal data and to sensitive data, fundamentals of genetic identify. Genetic identify understood as the projection of personal identify. In view of this, it is essential to review the national literature in the light of the constitutional principle of human dignity and fundamental rights, such as the right to life, health, intimacy, privacy and the free development of personality. In turn, a review and analysis of current Brazilian legislation, as well as the identification of guidelines, recommendations and international regulations, are constructs that support and contribute to the understanding of the relevance and pertinence of the subject of personal data protection, particularly human genetic data, demanding the legal support from the principles of the democratic State based on the rule of law. Finally, it is concluded that the protection of human genetic data in biobank activities is deserving of specific legislation, which includes measures of coherence in case of violation of the principle of human dignity and of the fundamental rights implied, that guarantees the integrity of the participant of the research and their personal rights, that imposes to the researchers, the participants, the research institutions and universities and the State, the duties and limits of action in relation to human life and health. Therefore, a specific infraconstitutional legislation, effective in the legal and effective protection in its implementation.